1995
DOI: 10.1007/bf01682038
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-unrestricted hematologic response to granulocyte colony-stimulating factor in a patient with refractory anemia with excess blasts

Abstract: We report a patient with refractory anemia with excess blasts who showed a lineage-unrestricted hematologic response to granulocyte colony-stimulating factor (G-CSF). After 17 months of a stable disease state, the patient developed pneumonia, progression of cytopenia, and reduced cellularity and blast mass in the bone marrow. He was given G-CSF to overcome the pneumonia. Not only the neutrophil count, but also the platelet count increased soon after initiation of the G-CSF therapy; both counts became normal on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Histologic sections of the bone marrow, which were prepared from the aspirated bone marrow and stained with haematoxylin–eosin, were available for 14 RA cases, seven RAEB and 10 RAEB‐t cases. The method for preparing the histologic sections, from which contamination by peripheral blood was well‐eliminated, and examples of the histologic sections were reported previously ( Yokose et al , 1995 ; Tamura et al , 1997 ). These sections were examined with a microscope connected to a Micro‐Videomat 2 (Zeiss, Oberkochen, Germany), using a relatively high‐power field (×400) to identify micromegakaryocytes as well as normal‐sized megakaryocytes.…”
Section: Methodsmentioning
confidence: 99%
“…Histologic sections of the bone marrow, which were prepared from the aspirated bone marrow and stained with haematoxylin–eosin, were available for 14 RA cases, seven RAEB and 10 RAEB‐t cases. The method for preparing the histologic sections, from which contamination by peripheral blood was well‐eliminated, and examples of the histologic sections were reported previously ( Yokose et al , 1995 ; Tamura et al , 1997 ). These sections were examined with a microscope connected to a Micro‐Videomat 2 (Zeiss, Oberkochen, Germany), using a relatively high‐power field (×400) to identify micromegakaryocytes as well as normal‐sized megakaryocytes.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been reported that hematological disorders in some patients with MDS improved following treatment with G-CSF (Nagler et al, 1995;Yokose et al, 1995). However, this mechanism has not yet been clari®ed.…”
Section: Discussionmentioning
confidence: 96%
“…Some cases with MDS show a quantitative hematological recovery of one or more cell lineages responding to G-CSF treatment (Nagler et al, 1995;Yokose et al, 1995). This mechanism has not yet been clarified.…”
mentioning
confidence: 96%